B.I CHECKING SEBAGAI ALAT BUKTI DALAM PEMBUKTIAN SEDERHANA PERKARA KEPAILITAN - Lumban Gaol, Christopher Panal (Fiat Iustitia : Jurnal Hukum, 2020)
The business world needs certainty in carrying out economic activities that are the backbone of the economy, and business people need legal certainty so that there will be no multiple interpretations in carrying out these business activities. Banking is a business activity in the field of financial services that really needs the law to run its business. If there is no law, public fund raising will be chaotic. These activities require supervision and also require authority so that they can run in an orderly and calm manner. Legal uncertainty will be detrimental to all parties, be it the state, the people and business people. If you want to see further, surely the investment will not go well, which means that money from abroad will not enter Indonesia. Strengthening in law in the field of business is a must and also a lot of attention from developed countries. Evidence is a tool that can be used to strengthen the argument in the procedural law. The procedural law in a bankruptcy case has a difference, it must be proven simply. The normative juridical approach with analytical descriptive is the research method used in this paper. Simple proof of the existence of two or more creditors can be done through B.I Checking. Because the data is managed by the central bank in Indonesia, so the validity of the data can be guaranteed, and the data can be accessed via the internet, so that it can be easily Â taken and displayed in court.